Polymerization Shrinkage of Short Fiber Reinforced Dental Composite Using a Confocal Laser Analysis - Miura Daisuke; Ishida Yoshiki; Shinya Akikazu (MDPI, 2022)
The purpose of this study was to investigate the polymerization shrinkage of short fiber reinforced composite (SFRC) using a multicolor confocal displacement laser that can measure the polymerization shrinkage with high accuracy. The three types of SFRCs used in this study were XD (Ever X Flow Dentin), XB (Ever X Flow Bulk), and XP (EverX Posterior). In addition, CF (Clearfil majesty ES Flow) with hybrid type filler was used as a control. The measured values of the final polymerization shrinkage rate and amount of polymerization shrinkage rate when the polymerization shrinkage rate became constant (less than 0.1 mu m/s) were approximated for all SFRCs. XP had a large aspect ratio of glass fiber filler and showed a significant difference from XD with a small aspect ratio (p < 0.05). There was no significant difference in the measured value of time when the polymerization contraction reached a constant speed (0.1 mu m/s or less) for all SFRCs (p > 0.05). There was no significant difference in the measured values of polymerization shrinkage rate after the polymerization shrinkage reached a constant rate for all SFRCs (p > 0.05). These results show that glass fiber with large aspect ratio can alleviate polymerization shrinkage stress. The polymerization behavior of SFRC was found to be dependent on the amount of glass fiber filler, aspect ratio, and orientation.